Optimizing Employee Performance through Work Environment and Work Motivation in the Denim Inspect Department of PT Apac Inti Corpora - Defriansyah, Muhammad Naufal; Febriana, Artha; Puji Purwatiningsih, Aris; Linati Haziroh, Awanis (UMSurabaya Publishing, 2025)
Employee performance refers to the extent to which employees accomplish their tasks within a specific period. This study investigates the influence of democratic leadership style, work environment, and employee motivation on employee performance in the Inspect Denim Department of PT. Apac Inti Corpora. Data were collected using a Likert-scale questionnaire distributed to 80 employees through a total sampling method, and analyzed with multiple linear regression. The results show that: (1) democratic leadership style has a statistically less significant effect on employee performance, (2) the work environment has a positive and significant impact on employee performance, and (3) employee motivation also has a positive and significant effect on performance. These findings highlight the importance of supportive working conditions and motivation in enhancing employee performance, while indicating that leadership style may play a less central role in this context